1999
DOI: 10.1046/j.1365-2923.1999.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Students conducting consultations in general practice and the acceptability to patients

Abstract: The results of this study are very reassuring concerning the acceptability to patients of consulting with medical students and are more favourable than those reported for studies of students being present in consultations by GPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 3 publications
3
60
0
2
Order By: Relevance
“…Tel: (519) 579-1012; email: kpassaperuma2007@meds.uwo.ca 2003). A significant minority (17-36%) felt they benefited from or preferred having students involved (Cooke et al 1996;Bentham et al 1999;Hajioff & Birchall 1999). York et al (1995) reported that 92% of inpatient Surgery patients felt they had benefited from the patient-student interaction.…”
Section: Practice Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tel: (519) 579-1012; email: kpassaperuma2007@meds.uwo.ca 2003). A significant minority (17-36%) felt they benefited from or preferred having students involved (Cooke et al 1996;Bentham et al 1999;Hajioff & Birchall 1999). York et al (1995) reported that 92% of inpatient Surgery patients felt they had benefited from the patient-student interaction.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Also, Chipp et al (2004) found that patients were less comfortable with student involvement in more invasive clinical tasks. Although the majority of patients did not have a preference for student gender, those who did were mostly female (King et al 1992;Cooke et al 1996;Bentham et al 1999;Chipp et al 2004). While the breadth of the current literature includes studies conducted within several individual specialties, no study has ever directly compared patient comfort levels and attitudes regarding medical student involvement between specialties to investigate for inter-specialty differences.…”
Section: Practice Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further finding concerns patient perceptions of doctor gender. In one GP study [8], 86% respondents (n=130) expressed '...no concern' about gender, and these results are reflected in secondary care [9]. As mentioned, specific references to communication and gender are infrequent.…”
mentioning
confidence: 99%
“…79 80 One study that had a low response rate, reported no decrease in clinical productivity (number of patients/hour) or overtime hours, while clinical productivity correlated to the number of patients seen independently by the student. 28 Impact on patients in the teaching practice The impact on patients was reported by eight papers from the UK, [86][87][88] the USA, 31 Australia, 89 Israel, 90 Sweden 91 and Austria 29 (table 6). All of them used questionnaire surveys with attitudinal statements and Likert scales and are non-comparative, except for two studies where patients seen with students were compared to those seen without students or before and after the consultation with a student.…”
mentioning
confidence: 99%